PERAN LKP ASY SYIFA DALAM MENINGKATKAN KETERAMPILAN MASYARAKAT DI BIDANG TEKNOLOGI KOMPUTER - Dwi Rahayu Pitaloka; Sucitra; Wasis Wijayanto (Jurnal Obor Penmas: Pendidikan Luar Sekolah, 2026)
This study aims to analyze the role of ASY SYIFA Course and Training Institute (LKP ASY SYIFA) in improving community skills in computer technology. The research employed a qualitative approach using a case study method conducted at LKP ASY SYIFA in Pati Regency. Data were collected through observation, semi-structured interviews, and documentation, and analyzed using data reduction, data display, and conclusion drawing techniques. The findings indicate that LKP ASY SYIFA plays a significant role in enhancing community computer skills through interactive learning strategies, systematic training management encompassing planning, implementation, and evaluation, as well as the provision of adequate facilities and relevant learning modules. The training programs provide tangible benefits, including improved technical skills, increased self-confidence, and better work readiness among participants. Therefore, LKP ASY SYIFA contributes substantially to community empowerment and the strengthening of digital literacy in rural areas.